Cuidando do cuidador: um espaço potencializador de educação permanente com equipes de estratégia de saúde da família - Alcântara, Débora Barbosa e [UNIFESP] (2015)
With the elaboration of SUS, afther the Health Reform, new paradigms have become a part of the routine of health professionals in Brazil. the medical logic focused and the hospital-centric system, lose space out to the longitudinal follow-up, prevention and health promotion to people, regarding the health concept. The new reality makes the profile of the new working professionals adapt to new paradigms that are devoted to life production. Spaces, named by the Ministry of Health, such as Permanent Education ("Educação Permanente"), were created to facilitate this passage. The current study decided to discuss how this tool has been used, to propose a mechanism that in fact enhances the spaces of the Continuing Education in Primary Health Care ("Educação Permanente na Atenção Básica em Saúde"). It has been presented the possibility of eight meetings in the workshop format, intended to improve and facilitate the group processo of two teams of Family Health Strategy, so that they meet their potentials and difficulties regarding the learning needs, uniquely presented, and thus enabling their qualifications to act in this "new" SUS. The chosen method to experiencie this collective process and research was the mapping within the research-intervention, allowing that I could move between the intervention and the observation by lurking around. The meetings have provided delicate changes on the health work of these teams and the perceptions that these have on theis collective. To set these meetings through narratives, photograph and video records, brought an aesthetic perspective to the events, unraveling in the processes, the relevance of the reserach as being a space that has created a power to listen, recognize and investigate situations brought by workers and as an opportunity to "caring for the carers", in the daily work.